2020
DOI: 10.1021/acs.iecr.9b06667
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Reactions of Fe(CO)5, Fe(C5H5)2, and TTIP as Precursors for the Spray-Flame Synthesis of Nanoparticles in Partial Spray Evaporation at Low Temperatures

Abstract: Flame spray pyrolysis is an important method of nanoparticle manufacturing. Reactions of the precursor and the solvent determine which intermediates can contribute to particle formation. To investigate the chemical interaction between the solvent and the precursor during the partial evaporation of the spray preceding ignition, precursor solutions were sprayed into an externally heated flow reactor. The thermal decomposition of the precursors Fe(CO) 5 , Fe(C 5 H 5 ) 2 , and Ti(i-OC 3 H 7 ) 4 in solutions of xyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…However, the bi-component droplet heating and evaporation model was validated for single bi-component ethanol/water droplets in air [12] with experimental results from Ma et al [25] so that for the present system under consideration, numerical results of the physical process as well as a parameter study are presented. Following the conditions in experimental studies of FSP [7,5,4], initial droplet radii of 5 µm, 10 µm, 25 µm, and 50 µm are considered for ambient air temperatures of 800 K and 1200 K and relative velocities of 4 m/s and 8 m/s. Also, three different initial mass fractions of TTIP in the precursor solution are considered, namely, 0.025, 0.155 and 0.25.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the bi-component droplet heating and evaporation model was validated for single bi-component ethanol/water droplets in air [12] with experimental results from Ma et al [25] so that for the present system under consideration, numerical results of the physical process as well as a parameter study are presented. Following the conditions in experimental studies of FSP [7,5,4], initial droplet radii of 5 µm, 10 µm, 25 µm, and 50 µm are considered for ambient air temperatures of 800 K and 1200 K and relative velocities of 4 m/s and 8 m/s. Also, three different initial mass fractions of TTIP in the precursor solution are considered, namely, 0.025, 0.155 and 0.25.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [4] experimentally examined the micro-explosion mechanism of isolated TTIP/xylene droplets and observed that TTIP does not react with water vapor produced during the combustion process. In experiments by Gonchikzhapov and Kasper [5], the thermal decomposition of a spray consisting of different precursor solutions, for instance iron pentacarbonyl, ferrocene, and TTIP in solutions of o-xylene or ethanol was studied, and it was found that in solutions of TTIP and o-xylene, there is no chemical interaction between the precursor and the solvent in the liquid phase. Abdelsamie et al [6] performed direct numerical simulations of a configuration closely related to the SpraySyn burner [7] using a TTIP/ethanol precursor solution to produce TiO 2 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the sampling nozzle orifice is being gradually clogged by condensed matter during the experiment, reducing the nozzle sampling capacity and limiting the extent to which the sensitivity can be improved via longer signal accumulation times . The clogging of the sampling orifice is commonly diminished by limiting the experiments to relatively low precursor loads. , Protection of the probe orifice from clogging by particles using an automatic cleaning system was demonstrated by Gonchikzhapov and Kasper, who used TOF–MS with microprobe sampling to investigate the chemical interaction between the solvent and Fe­(CO) 5 , Fe­(C 5 H 5 ) 2 , and Ti­(i-OC 3 H 7 ) 4 precursors during partial evaporation of the spray preceding the ignition.…”
Section: Laser Spectroscopy and Mass Spectrometry Methods For Elucida...mentioning
confidence: 99%
“…41 The clogging of the sampling orifice is commonly diminished by limiting the experiments to relatively low precursor loads. 41,142 Protection of the probe orifice from clogging by particles using an automatic cleaning system was demonstrated by Gonchikzhapov and Kasper, 143 who used TOF−MS with microprobe sampling to investigate the chemical interaction between the solvent and Fe(CO) 5 , Fe(C 5 H 5 ) 2 , and Ti(i-OC 3 H 7 ) 4 precursors during partial evaporation of the spray preceding the ignition. Gerasimov et al 49,142 studied an atmospheric pressure H 2 / O 2 /N 2 flame doped with Fe(CO) 5 using EI−MBMS with a quadrupole mass spectrometer.…”
Section: Molecular Beam Mass Spectrometry (Mbms)mentioning
confidence: 99%